2020
DOI: 10.3390/vaccines8020165
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Healthcare System-Based Interventions in Improving the Uptake of Influenza Vaccination in Healthcare Workers at Long-Term Care Facilities: A Systematic Review

Abstract: Healthcare workers (HCWs) in long-term care facilities (LTCFs) can represent a source of influenza infection for the elderly. While flu vaccination coverage (VC) is satisfactory in the elderly, HCWs are less likely to be vaccinated. There is no definitive evidence on which types of healthcare system-based interventions at LTCFs would be more useful in improving the vaccination uptake among HCWs. We performed a systematic review in different databases (Pubmed, Cochrane Database of Systematic Reviews, Health Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“… 36 , 37 Vaccination mandates have proven to be the most impactful intervention for increasing SIV among HCWs. 38 In Switzerland, unlike some countries, there are no mandatory vaccines, and many HCWs are opposed to mandatory vaccination. 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 , 37 Vaccination mandates have proven to be the most impactful intervention for increasing SIV among HCWs. 38 In Switzerland, unlike some countries, there are no mandatory vaccines, and many HCWs are opposed to mandatory vaccination. 39 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 42 Similar to that in previous studies, facilitated access to vaccination most likely played a role, as 88.7% of pharmacists were vaccinated in a pharmacy. 38 , 41 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that the included studies assess the effectiveness of influenza vaccination in countries where vaccination coverages are diverse. In European countries vaccination is generally recommended in the elderly, adults with chronic conditions or healthcare workers to reduce transmission [ 35 ], but influenza vaccination coverage rates are generally still not adequate [ 36 ]. In England, where influenza vaccine is offered to all people with chronic conditions, Vamos et al found that vaccination coverage ranged from 63.1% in 2008/09 to 69.0% in 2006/07 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, workplace vaccine mandates have proven the most successful intervention at increasing influenza vaccination, and this success was enhanced when combined with other interventions, such as education [35]. On the other hand, influenza outbreaks are relatively common, historically occurring in 30-60% of long-term care facilities each year [36] and studies have been inconclusive so far about whether vaccinating HCWs against influenza actually prevented infection [37].…”
Section: Pre-covid-19 Vaccine Hesitancy Among Healthcare Workersmentioning
confidence: 99%